WORKSHOP PUBLIKASI ILMIAH GURU SEKOLAH DASAR MELALUI PELATIHAN PENULISAN KARYA TULIS ILMIAH - Iqnatia Alfiansyah; Nataria Wahyuning Subayani; Arya Setya Nugroho (JUSEDA, 2020)
The purpose of this community service activity is to increase the productivity of elementary school teachers, especially UMG PGSD alumni in terms of writing scientific papers. As a young teacher, the enthusiasm for innovation should be motivated and facilitated so that young teachers who have entered the field, increasingly increasing their productivity and creativity. In order to become a teacher, it is not just about teaching material, but also research missions and innovators. In accommodating creativity and channeling the results of research in the form of scientific work, we from the PGSD undergraduate lecturer team are devoted to young teachers so that the research they have done is published. This community service activity is in the form of training in writing scientific papers in the form of scientific articles to publishing (publishing) scientific articles through online journals. The series of activities include, 1) Preparation, by preparing good KTI materials, 2) writing, by starting to write, guiding participants to learn and understand KTI, 3) Editing, by improving grammar, material substance and others, 4) Publications, KTI that has been revised is published in scientific journals, 5) the monitoring and evaluation stage, which is the stage for describing the revised KTI results to peers. The target outputs to be achieved are 1) Scientific Papers that have been compiled and revised are uploaded in online and print journals, at least national journals, 2) Add insight for teachers about national journals, 3) teach teachers to be more skilled in preparing scientific papers. The results of this activity are in the form of consultation articles, for teachers who already have a research article and feed back in the form of responses via Instagram with PGSD hashtag (#pgsdumg). The three teachers are Amelia Razanah from SDN Tlogopatut, Ika Lufianah from SDN Randuagung 2 and Fatma hajar Islamiyah from GKB HR 2. The articles owned will be published in journals managed by PGSD study programs namely JTIEE at a volume that will be determined by the journal manager. The expectation of the participants was that this kind of training was carried out routinely every semester in order to support the productivity and acquisition of functional teacher positions for career advancement.